Microstructure, biodegradable behavior in different simulated body fluids, antibacterial effect on different bacteria and cytotoxicity of rolled Zn–Li–Ag alloy. (27th May 2020) - Xu, Xuemei; Lu, Yujiao; Chu, Xin; Yan, Yang; Liu, Ying; Xu, Xiangchun; Luo, Xier; Chen, Liangjian; Li, Ding; Xiao, Tao; Yu, Kun
Abstract: Rolled Zn-0.8Li-0.2Ag(wt%) alloy as candidates for biodegradable materials. The biodegradable behavior of Zn-0.8Li-0.2Ag alloy in different solutions (Ringer's, DMEM, SBF and DMEMp) was investigated. The cytotoxicity of Zn-0.8Li-0.2Ag alloy and its antibacterial properties against staphylococcus aureus, enterobacter faecalis and candida albicans were evaluated. The results showed that Zn-0.8Li-0.2Ag alloy consists of zinc matrix and a LiZn4 secondary phase. The presence of Cl − causes locally corroded of Zn-0.8Li-0.2Ag alloy in Ringer's solution, and its corrosion resistance is lower than that of the alloy which is uniformly corroded in other solutions containing CO3 2− and PO4 3− . Zn-0.8Li-0.2Ag alloy is non-toxic and exhibits better antibacterial properties than the experimental reference group without silver.